2012
DOI: 10.1590/s0103-84782012005000017
|View full text |Cite
|
Sign up to set email alerts
|

Enraizamento de estacas lenhosas de três cultivares de mirtileiro com diferentes concentrações de AIB

Abstract: Comercialmente, a propagação do mirtileiro por meio de estacas é o método mais utilizado, proporcionando resultados diversos de acordo com a cultivar e a concentração de ácido indolbutírico (AIB) utilizada. Objetivou-se, com este trabalho, avaliar o efeito do ácido indolbutírico no enraizamento de estacas lenhosas de mirtileiro. O material utilizado constituiu-se de segmentos de ramos secundários, com quatro gemas e diâmetro médio de 4,5mm. O delineamento experimental foi completamente casualizado, em fatorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…For plant species that are difficult to root, such as blueberry, auxiliary techniques with growth regulators, such as indolebutyric acid (IBA), can be used [10]. Exogenous application of synthetic auxins is very common in vegetative propagation methods using cuttings as they act similar to the natural phytohormone [11].…”
Section: Introductionmentioning
confidence: 99%
“…For plant species that are difficult to root, such as blueberry, auxiliary techniques with growth regulators, such as indolebutyric acid (IBA), can be used [10]. Exogenous application of synthetic auxins is very common in vegetative propagation methods using cuttings as they act similar to the natural phytohormone [11].…”
Section: Introductionmentioning
confidence: 99%
“…According to Pires and Biasi (2003) and Fachinello et al (2005), synthetic auxins are used to favor root development, and the indolebutyric acid (IBA) is relatively stable and highly effective to a large number of species. However, studies have shown that the effect of exogenous auxins varies among species, cultivars and concentrations (Fischer et al, 2008;Trevisan et al, 2008;Vignolo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…O AIB é importante no desenvolvimento do sistema radicular de algumas espécies (PIZZATTO et al, 2011;VIGNOLO et al, 2012), em plantas com sistema radicular bem estruturado o AIB promove maior desenvolvimento da parte aérea, conforme observado por LOPES et al (2003) no enraizamento de acerola.…”
Section: Mean Values With the Same Lowercase Letters On A Line Or Uppunclassified